In vivo neurological assessment of sedative hypnotic effect of Coriandrum sativum L. seeds in mice. - Abdulrahman M Alshahrani (International Journal of Phytomedicine, 2015)
Ethnopharmacological relevance: seeds of Coriandrum sativum L. have been used in the traditional medicine to relieve stress and other neurological disease conditions. Aim of the study: The present study was under taken to evaluate the sedative hypnotic response of ethanolic extract of seeds of Coriandrum sativum L. (CSEE) in mice. Materials and methods: seeds of Coriandrum sativum L. Ethanolic extract was screened for sedative hypnotic response by using potentiation of Pentobarbital sleeping time at doses of 100mg/kg, 150mg/kg and 200 mg/kg. Saline and Pentobarbital sodium were employed as negative and positive control groups, respectively. Results: Ethanol extract increases Pentobarbital sodium induced sleeping time at dose of 100 mg/kg, 150 mg/kg and 200 mg/kg by 106 %, 111 % and 114% respectively as compared to negative control group and by 06 %, 11% & 14% respectively as compared to positive control group Conclusion: from present study finding it is found that seeds of Coriandrum sativum L. potentiate the sedative hypnotic efficacy in mice.